Quorum sensing and surface attachment in Acinetobacter baumannii - Lopez Martin, Mario (2020)
Acinetobacter baumannii is a Gram-negative nosocomial pathogen that causes a wide range of infections, including ventilator-associated pneumonia and soft tissue infections, mostly in seriously ill patients. Even though several virulence-associated factors have been described, the exact mechanisms of infection and the overall regulation of A. baumannii virulence are still poorly understood. One of the regulatory systems involved in virulence in many other pathogenic bacteria is quorum sensing (QS), a cell density-dependent bacterial communication system that relies in the accumulation of an extracellular signal. In Gram-negative bacteria, these are usually N-acyl-homoserine lactones (AHLs)) and they facilitate coordination of gene expression within a bacterial population. A. baumannii possesses a single LuxR/LuxI-type QS locus, named AbaR/AbaI, that, despite being reported in previous publications to be involved in surface motility and biofilm formation, remains poorly characterized.